Designing the Internalizing and Externalizing Behavior Model of Adolescents Based on Early Maladaptive Schemas with the Mediating Role of Coping Responses - Sobhani, Maryam; Haji Alizadeh, Kobra; Zarei, Eghbal; Amirfakhraei, Azita (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim: The present study was conducted with the aim of designing a model of internalizing and externalizing behavior of adolescents based on the early maladaptive schemas with the mediating role of coping responses. Methods: The research method was descriptive and structural equation modeling. The statistical population of the current study was all the male and female students of the second secondary level in the 3rd district of Tehran in the year 1400. The number of sample people was 400 students who were selected by cluster method (4 schools). The research tools included the list of child behavioral disorders (Achenbach, 1991), the questionnaire of early maladaptive schemas (Yang, 2003) and the questionnaire of coping strategies (Lazarus and Folkman, 1988). The collected data were analyzed by structural equation modeling method. Results: The results of data analysis showed that the model has a good fit. Also, early maladaptive schemas have a direct effect on internalizing behavior, the relationship between primary maladaptive schemas and internalizing behavior is directly equal (t = 4.98 and β = 0.43). Early maladaptive schemas have a direct effect on externalizing behavior, the relationship between early maladaptive schemas and externalizing behavior is directly equal (t = 1.99 and β = 0.13). In connection with the existence of an indirect effect of early maladaptive schemas on the internalizing behavior of adolescents through coping strategies, it has been confirmed with 95% confidence (p<0.05). Conclusion: the results showed that the hypothesis proposed in connection with the existence of an indirect effect of early maladaptive schemas on the externalizing behavior of adolescents through coping strategies was confirmed with 95% confidence (p<0.05).